Pengaruh Penerapan Video Animasi Riko The Series terhadap Minat dan Prestasi Belajar Siswa pada Mata Pelajaran Al-Qur’an Hadits (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to test the effect of the animated video "Riko the series" on the interest and learning achievement of class VII students of MTs Mallari in the subject of Al-Quran Hadith. This study uses an experimental quantitative method with a non-equivalent control group design. This study uses 40 samples with a saturated sampling technique. And this study collects data through observation, questionnaires, tests, and documentation and analyzes using an independent sample t-test. The results showed a significant increase in student interest and learning achievement in the experimental class using animated videos. The average interest in learning increased from 60.15 to 72.80, and learning achievement from 35.50 to 67.00. Statistical analysis with SPSS 25 confirmed a significant effect (p